Exploring community engagement and sustainability dynamics in the design and development of tahfiz institutions: case study of Indonesia - Awang, Arita Hanim; Ab Jalil, Nurlelawati; Salleh, Nurul Hamiruddin; Ab Jalil, Habibah; Salim, Siti Suria (Faculty of Humanities and Social Sciences , Prince of Songkla University, Pattani Campus, 2023)
This study conducts a comparative investigation into three Indonesian Tahfiz institutions. The purpose of the study visit is to identify the local factors that influence the design and development of the pesantren in relation to community and sustainability practices. The method employs a qualitative research framework involving case study visits, on-site observations, and in-depth interviews. The results unveil both similar patterns and distinct variations that significantly shape the operational paradigms of the three pesantren. Students serving as prayer leaders (Imam) in nearby mosques is a common practice that strengthens ties between the many institutions in the community. Additionally, these pesantren prioritize alumni involvement as educators and administrators, reflecting their dedication to community engagement. In the aspect of sustainability practices, contextual variations are shown, with each pesantren developing their own paths in response to the needs of their specific situation. Institutional philosophies are a major source of architectural and spatial arrangements that also show a different approach of each pesantren. As a conclusion; this study deepens the understanding of the complex processes behind the evolution of the Tahfiz Institution in Malay Archipelago such as in Indonesia by emphasizing the blending of tradition and modernity, demonstrating extensive community integration, and emphasizing adaptive sustainability considerations.